Computer Networks / Fourth Edition - Tanenbaum, Andrew S. (Pearson Education Limited, 2003)
This book reflects the newest and most important networking technologies. Preface, Introduction, The Physical Layer, The Data Link Layer, The Medium Access Control Sublayer, The Network Layer, The Transport Layer, The Application Layer, Network Security, Reading List and Bibliography, Index.